Freedom of access to government information in Africa: trends, status and challenges. (20th November 2017) - Asogwa, Brendan Eze; Ezema, Ifeanyi Jonas
Abstract : Purpose: Agitation for adoption of freedom of access to government information is an emerging issue in Africa and has gathered momentum since 2000 when South Africa passed the first freedom of information (FoI) law in the continent. This paper aims to discuss the extent of passage of FoI laws in Africa, the reality of their implementation in some of the countries and the critical challenges and recommendations. Design/methodology/approach: A document analysis approach was adopted for gathering vital information on the realities and challenges of FoI implementation in Africa. Literature on the concepts, principles and practice of FoI were reviewed, and relevant facts and figures were extracted to buttress the authors' argument. Findings: Only 14 (25.5 per cent) of the 55 countries in Africa had signed FoI law as on January 31, 2015; 16 (29.0 per cent) are still lobbying, while 25 (45.5 per cent) of the states had no significant plan yet. Political factors like colonial legacy, poor leadership, inexperienced record managers for the implementation of FoI Acts (FoIA), corruption and hydra-headed clauses such as "national security, and other privacy rights" impede access to government records in Africa. The paper recommended among others that African countries should amend restrictive laws that continue to impede full implantation of FoI laws. Practical implications: Implementation of the provisions in the FoIA in Africa will not be realistic unless those restrictive clauses that hinder citizens from freely accessing government information are reviewed in line with free access to information. Originality/value: This paper appears to be the first to review the status of FoIA in Africa since the first right to information laws were signed in the continent.